The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1039/d2ob01841a
|View full text |Cite
|
Sign up to set email alerts
|

The arylvinylpyrimidine scaffold: a tunable platform for luminescent and optical materials

Abstract: The incorporation of electron-withdrawing pyrimidine rings within p-extended systems allows access to a wide variety of fluorescent push-pull molecules that display emission properties highly sensitive to external stimuli. A suitable...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 96 publications
(153 reference statements)
0
5
0
Order By: Relevance
“…In heptane, it is worth mentioning that in the case of 1 and 2, the emission bands recorded at 298 K and 77 K are quasi superimposable, which would suggest a similar energy level for 1 LE and 1 CT in this solvent at room temperature. In toluene, a strong hypsochromic shift occurs for 1 and 2 when freezing the solution, indicating the sole presence of 1 CT at room temperature and 1 LE at 77 K. The case of 3 seems to be more elusive. In toluene, a single band is observed at 77 K, whose maximum emission wavelength is reminiscent of a high energy band at room temperature (l em = 439 nm vs. 438 nm for 3 at 77 K and 298 K, respectively).…”
Section: Photophysical Propertiesmentioning
confidence: 97%
See 1 more Smart Citation
“…In heptane, it is worth mentioning that in the case of 1 and 2, the emission bands recorded at 298 K and 77 K are quasi superimposable, which would suggest a similar energy level for 1 LE and 1 CT in this solvent at room temperature. In toluene, a strong hypsochromic shift occurs for 1 and 2 when freezing the solution, indicating the sole presence of 1 CT at room temperature and 1 LE at 77 K. The case of 3 seems to be more elusive. In toluene, a single band is observed at 77 K, whose maximum emission wavelength is reminiscent of a high energy band at room temperature (l em = 439 nm vs. 438 nm for 3 at 77 K and 298 K, respectively).…”
Section: Photophysical Propertiesmentioning
confidence: 97%
“…Styrylpyrimidine derivatives with electron-donating groups have been extensively studied in the last two decades as push–pull chromophores. 1 This family of chromophores encompasses in particular linear 4-styrylpyrimidines, 2 V-shaped quadrupolar 4,6-distyrylpyrimidines, 2 a ,3 tripodal 2,4,6-tristyrylpyrimidines 4 and other arylvinylpyrimidines. 5 Many of these compounds exhibit photoluminescence properties that can be tuned by external stimuli such as polarity or pH.…”
Section: Introductionmentioning
confidence: 99%
“…Azole and benzazole ESIPT-capable derivatives are workhorses in the area of ESIPT studies. The most common molecular pattern of these compounds which is widely relied upon in the design of ESIPT dyes includes the proton-accepting azole/benzazole moiety combined with the proton-donating 2-hydroxyphenyl group or its analogues introduced in the α position to the azolic N atom. In contrast, pyrimidine derivatives are relatively rarely used for the design of ESIPT-fluorophores in comparison with azole and benzazole ones. , However, being combined with suitable proton-donating groups, they can serve as proton-accepting moieties. ,, Moreover, introducing additional donor groups in the pyrimidine core can lead to more complex molecular architectures of pyrimidine-based compounds suitable for binding metal ions and providing numerous sites for protonation, including isomeric ones. ,, In turn, the synthesis of isomeric ESIPT-capable compounds allows researchers to shed more light on the impact of structural factors on ESIPT and on relationships between ESIPT and luminescence. The coordination of conventional dyes and ESIPT emitters to metal ions with d electronic configuration such as Zn 2+ is known to enhance the quantum efficiency of emission. Earlier we demonstrated that emissions of 4-(1 H -pyrazol-1-yl)-6-(2-hydroxyphenyl)­pyrimidines and 2-(2-hydroxyphenyl)-4-(1 H -pyrazol-1-yl)­pyrimidines, which belong to two different isomeric families (Chart ), share such a common feature as dual emission associated with singlet-to-singlet and triplet-to-singlet transitions, which is contributed by anti-Kasha fluorescence of the tautomeric form. ,, However, their coordination behavior toward Zn 2+ ions appeared to be quite different, whereas the 4-(1 H -pyrazol-1-yl)-6-(2-hydroxyphenyl)­pyrimidine derivative can bind Zn 2+ ions through the N,N-site of the molecule, which produces multicolor emission of the complex, 2-(2-hydroxyphenyl)-4-(3,5-dimethyl-1 H -pyrazol-1-yl)­pyrimidine derivatives cannot do this. We associated this with steric effects imposed by methyl and phenyl substituents introduced in positions 3 and 5 of the pyrazolyl group.…”
Section: Introductionmentioning
confidence: 99%
“…By engaging the nitrogen atoms with lone pairs in complexation, protonation, hydrogen bonding and so on, the electron-withdrawing behavior can be tuned and, hence, pyrimidine-based molecules are considered as excellent candidates for optical applications. 34 In the present work, we discuss the design and development of a pyrimidine-based fluorescent probe, HSAL, showing dual sensing behavior towards Al 3+ /Zn 2+ ions. The probe contains pyrimidine and imine nitrogens along with phenolic hydroxyl moieties which provide effective coordination sites for the cations.…”
Section: Introductionmentioning
confidence: 99%
“…By engaging the nitrogen atoms with lone pairs in complexation, protonation, hydrogen bonding and so on, the electron-withdrawing behavior can be tuned and, hence, pyrimidine-based molecules are considered as excellent candidates for optical applications. 34…”
Section: Introductionmentioning
confidence: 99%